2017
DOI: 10.1039/c6se00026f
|View full text |Cite
|
Sign up to set email alerts
|

CeO2@C derived from benzene carboxylate bridged metal–organic frameworks: ligand induced morphology evolution and influence on the electrochemical properties as a lithium-ion battery anode

Abstract: Spherically shaped MOF-derived CeO2@C shows a superior performance as a lithium-ion battery anode with high specific capacity, rate performance and cycling stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 83 publications
2
13
0
Order By: Relevance
“…It is known that the carboxylate functional groups present in the organic ligand (benzene-1,4-dicarboxylate) can act as the nucleation sites for the MOF crystal growth. , Here, PVP plays a crucial role during the solvothermal synthesis process as a structure-directing agent by regulating the growth and assembly of the unit structures and also acts as a stabilizing agent during the metal–ligand coordination. , The effect of PVP on the morphology is clearly manifested in the field emission scanning electron microscopy (FESEM) images of the synthesized MOFs (Figure ). It is observed that the morphology of Mg–1,4-BDC MOF consists of small platelike particles assembled in a random fashion (Figure a), whereas large thick plates in orderly fashion are observed for PMg–1,4-BDC MOF (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the carboxylate functional groups present in the organic ligand (benzene-1,4-dicarboxylate) can act as the nucleation sites for the MOF crystal growth. , Here, PVP plays a crucial role during the solvothermal synthesis process as a structure-directing agent by regulating the growth and assembly of the unit structures and also acts as a stabilizing agent during the metal–ligand coordination. , The effect of PVP on the morphology is clearly manifested in the field emission scanning electron microscopy (FESEM) images of the synthesized MOFs (Figure ). It is observed that the morphology of Mg–1,4-BDC MOF consists of small platelike particles assembled in a random fashion (Figure a), whereas large thick plates in orderly fashion are observed for PMg–1,4-BDC MOF (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…A broad peak at 2θ = 28.7° appeared in all CeNPs@MOF patterns which corresponds to the CeNPs (111) reflection, indicating the immobilization of the NPs within the MOF (Figure a inset, Figure S4b). This peak broadening might originate from the small particle size and the existence of lattice strain . The full range XRD pattern of CeNPs (Figure S2) shows the characteristic (111), (220), and (311) reflections with broad peaks indicating the formation of small sized particles …”
Section: Results and Discussionmentioning
confidence: 99%
“…This peak broadening might originate from the small particle size and the existence of lattice strain. 21 The full range XRD pattern of CeNPs (Figure S2) shows the characteristic (111), (220), and (311) reflections with broad peaks indicating the formation of small sized particles. 22 FTIR spectra of the samples reveal the characteristic bands of the MOF linker and CeNPs (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…Althoughc apacity fading occurredd uring cycling, the high specific capacity of CeLipma still providesapromising choice for novel electrode materials. Compared with other electrodes assembled from rare-earth-based materials, the reversible capacityo fC eLipma is highert han those of CeO 2 @C [47] and Tb 2 (H 2 dobdc) 3 (dmf) 4 [26] under similarc onditions, which is even bettert han that of certain compounds without rare-earth metals, [40,41,45] suggesting that rare-earth-based compounds as electrode materials deserve more in-depthstudy (Table 3).…”
Section: Electrochemical Performancesmentioning
confidence: 99%